2016
DOI: 10.1007/s13760-016-0655-9
|View full text |Cite
|
Sign up to set email alerts
|

Addenbrooke’s cognitive examination test for brief cognitive assessment of adolescents suffering from migraine with aura

Abstract: The aim of this study was to assess the role of the Addenbrooke's cognitive examination test (ACE-R) in the evaluation of cognitive status in migraineurs interictally. A total of 44 adolescent patients and 44 healthy controls, matched by age and gender, have undergone ACE-R testing. Migraineurs were additionally questioned about migraine aura features and presence of higher cortical dysfunctions (HCD) during an aura. According to the questionnaire results, patients were subsequently divided into HCD and Non-HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In patients with migraine, there were significant lower scores in semantic verbal fluency (“animals” subtest), but not in phonemic verbal fluency. Petrusic et al ( 43 ) recruited 74 adolescents (age range 13–19 years) who suffered from migraine with aura. Compared with healthy subjects, performances in verbal fluency, but not in language, were lower in patients than in control subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with migraine, there were significant lower scores in semantic verbal fluency (“animals” subtest), but not in phonemic verbal fluency. Petrusic et al ( 43 ) recruited 74 adolescents (age range 13–19 years) who suffered from migraine with aura. Compared with healthy subjects, performances in verbal fluency, but not in language, were lower in patients than in control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on migraine with aura, Petrusic et al ( 43 ) showed significantly lower performance in memory skills in adolescents suffering from migraine with aura compared with healthy subjects. As for language, the authors did not evidence significant association between the presence of higher cortical dysfunctions, frequency and duration of aura and the memory skills (evaluated by the “ACE-R test”) ( 43 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Migraine with aura (MwA) is a worldwide highly prevalent disorder that can have a tremendous impact on everyday life [ 1 , 2 ]. Although it is well known that during MwA attack cognitive dysfunction is present in various forms, recent studies also suggest that MwA patients could suffer from subtle cognitive changes during the interictal period [ 3 6 ]. Furthermore, it is known that cortical spreading depression, which is a pathophysiological substrate of migraine aura, could disrupt cortical function and also could be a cumulative risk factor for cerebrovascular events [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the previous studies the impairment of psychomotor abilities, attention and verbal memory, have been also found [122], which may be due to the damage caused by migraine. Comparing adolescent migraineurs and healthy groups using the Addenbrooke's Cognitive Test, the overall performance in the migraine group was significantly lower, resulting from significantly worse performance in the verbal fluency and memory tasks [123]. In our previous study, a poorer performance in associative learning and an extensive impairment in generalization was observed in adult migraineurs without aura.…”
Section: Migraine and Cognitive Functionsmentioning
confidence: 63%
“…In a previous fMRI study, it has been found that migraine has a negative effect on the proper functioning of the BG and that this damage is proportional to the frequency of attacks [100]. It was described in another study that volumes of the right globus pallidus, left globus pallidus, and left putamen were significantly smaller in migraine patients (with aura) than in healthy controls [123,133]. Another research group examined persons living with migraine without aura and concluded that the volume of the nucleus accumbens and caudate nucleus of patients was significantly smaller than that of controls [97].…”
Section: Discussionmentioning
confidence: 90%